A replicable, low‐burden mechanism for observing, recording, and analysing mother–child interaction in population research. (19th August 2018) - Levickis, Penny; Reilly, Sheena; Girolametto, Luigi; Ukoumunne, Obioha C.; Wake, Melissa
Abstract: Background: There is growing evidence that specific styles of parent–child interaction benefit child development, particularly child language development. Direct observational techniques help clarify the behaviours and styles within parent–child interactions that may influence child language outcomes; however, these techniques tend to be labour‐intensive and costly. We report on the development of a replicable, low‐burden mechanism for observing and coding specific maternal linguistic behaviours in a population‐based cohort of 2‐year‐olds. Methods: The coding scheme was developed as part of a prospective, longitudinal study examining the associations between maternal responsive behaviours and child language outcomes in slow‐to‐talk toddlers. In the first phase of the study, three coding systems were tested by coding five sample parent–toddler interactions and then comparing them based on (a) the ease of method and thus likely intrarater and interrater reliability and (b) the number of data points. The second phase was to demonstrate how the chosen method could be used in practice with a large at‐risk group of toddlers. Results: Of the three coding systems explored, the Observer® XT software was selected for ease of use and because detailed coding of free‐play videos could be achieved in close to real time. Intrarater and interrater reliability were established in 251 mother–child free‐play videos, producing high intraclass correlation coefficients of 0.95 to 0.99 for the six behaviours. Conclusions: The study provides evidence that numerous parent–child interactions can be rigourously yet efficiently coded without substantial information loss. The observational mechanism in the current study has been fully developed and is shown to be feasible for research purposes focusing on parent–toddler interactions. However, further testing of the observational mechanism is required to examine whether the same results could be produced if coding was conducted "live" and for shorter duration thereby making it readily useable for clinicians.